Losses of organic matter and nutrient by water erosion in cassava-based cropping systems - Ruppenthal, M; Leihner, D.E.; Steinmuller, N.; El-Sharkawy, Mabrouk A. (Cambridge University Press, 1997)
Erosion trials under natural rainfall were conducted at two locations in the Andean hillsides of south-west Colombia on moderate slopes. Sediment-bound losses of seven cassava (Manihot esculenta) cropping systems per cropping period ranged from 26 to 1726 kg ha?1 for organic matter, 0.9 to 65.5 kg ha?1 for total nitrogen, 0.03 to 2.1 kg ha?1 for exchangeable magnesium, 0.04 to 2.8 kg ha?1 forexchangeable potassium and 0.004 to 0.8 kg ha?1 for Bray-II phosphorus. Runoff water contributed substantially to total available potassium, magnesium and phosphorus losses. Concentrations of soluble phosphorus in runoff water from heavily eroded continuously clean-tilled fallow plots were slightly higher than from cropped and fertilized plots. Enrichment ratios for sediments from these highly aggregated Inceptisols were low. Sand-sized particles were selectively removed by water erosion. The higher proportion of nutrient losses with run-off water in our study stressed the importance of runoff control along with attempts to control soil losses and thus diminish both nutrient losses and surface water eutrophication.